Isolation of Megaritolactones and Other Bioactive Metabolites from ’Megaritiki’ Table Olives and Debittering Water. - Mousouri, Evgenia; Eleni Melliou; Prokopios Magiatis (J Agric Food Chem, 2014)
’Megaritiki’ is an olive cultivar widely used in Greece for the production of low polyphenol olive oil and table olives. To investigate possible metabolic differentiation in comparison with other varieties, the composition of ’Megaritiki’ olive fruits and wastewaters from the debittering procedure was studied. Moreover, the recovery of bioactive metabolites from wastewater using adsorption resin was studied to exploit this byproduct. Metabolites in fruits and wastewaters were monitored using NMR spectroscopy. The major constituents of wastewater were hydroxytyrosol-4-O-glucoside, 11-methyl-oleoside, hydroxytyrosol, and tyrosol but not oleuropein. Furthermore, wastewater afforded rengyoxide and rengyoside B, which are for the first time isolated from olives. The final edible olives, besides hydroxytyrosol and tyrosol, contained rengyoxide and cleroindicin C, which are the first isolated from the species, haleridone for the first time isolated from edible olives, and four metabolites, which are the first reported as natural products, megaritodilactone, megaritolactonic acid, methyl ester of megaritolactonic acid B, and megaritolactonol.